Traditional agroforestry systems and biodiversity conservation - Doddabasawa, -; Chitapur, BM; Murthy, M Mahadeva (Bangladesh Journal of Botany, 2018)
A survey was made to assess the biodiversity in traditional based agroforestry systems under rainfed agroecological situation in north eastern part of Karnataka, India and 27 tree species belonging to 15 families were recorded. Fabaceae was found to be the predominant family accounting for 11 species followed by Meliaceae and Rutaceae with 2 species each while other families had one species each. However, higher tree density per hectare was observed in Azadiractha indica (19.71) belonging to Meliaceae. Among the 27 species Sandal wood and Stain wood were listed in IUCN red list as threatened species. The highest number of families and species were observed in Koppal (11 and 20, respectively) closely followed by Yadgir district (10 and 20, respectively) while lower number of plant families and species were observed in Bidar district (6 and 11, respectively). Most of the species were used for timber (55.56%) purpose followed by fodder (48.15%), while 7.1 per cent were maintained for religious reasons.